Draft Annual Plan 1972-73, Part-II-Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 1972)
Union Territory of Pondicherry Statement Draft Annual Plan, 1972-73 Outlay and -Expenditure Draft Annual Plan Programme-Vise Outlay and Expenditure Union Territory of Pondicherry Draft Annual Plan, 1972-73 important Projects Costing Rs. Crores Rs. Crores and Above Draft Annual Plan, 1972-72 Checklist in Respect of Principal Projects Costing Rs.5 Crores and Above Union Territory of Pondicherry Draft Annual Plan, 1972-73 Physical Targets and Achievements Draft Annual 1972-73 Centrally Sponsored Schemes Scheme-Wise Outlay and Expenditure.
Revenue, Finance and Planning Department, Pondicherry